Eat pray love - Murphy, Ryan, 1965-; Salt, Jennifer, 1944-; Crudup, Billy, 1968-; Franco, James, 1978-; Bardem, Javier, 1969-; Roberts, Julia, 1967-; Davis, Viola, 1965-; Jenkins, Richard, 1947-; Gilbert, Elizabeth, 1969-; Columbia Pictures; Plan B Entertainment; Sony Pictures Home Entertainment (Firm) (Culver City, Calif. : Sony Pictures Home Entertainment, 2010)
After a very painful divorce, a woman risks everything and embarks on a journey around the world that becomes a quest for self-discovery.
Includes director's cut and original theatrical versions of the film.
DVD release of the 2010 motion picture.
Based on the book by Elizabeth Gilbert.
Special features: Movie making insights from Director Ryan Murphy.
Director of photography, Robert Richardson ; editor, Bradley Buecker ; music, Dario Marianelli.
Julia Roberts, Billy Crudup, James Franco, Javier Bardem, Viola Davis, Richard Jenkins.
Keywords: Gilbert, Elizabeth, -- 1969- -- Travel -- Drama; Travel writers -- United States -- Drama; Self-realization in women -- Drama; Self-actualization (Psychology) -- Drama; Voyages and travels -- Drama; Feature films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities